Effect of controlled release fertilizers on growth and leaf nitrogen status of immature rubber - George S; George V; Jessy M D; Punnoose K I (Natural Rubber Research, 2004)
The growth and leaf nitrogen status of immature rubber (Hevea brasiliensis) trees (clone RRII 105) which received 50 or 75 per cent of the recommended dose of N as NPK Mg tablets or 75 per cent as neem extract coated or neem cake mixed urea were comparable to those which received the full dose as prilled urea in two field experiments conducted in the central region of the traditional rubber growing tract of India, during 1994 to 1998. Single low dose of N applied as NPK Mg tablets was comparable to split doses of other fertilizers in terms of growth (girth) of the plants.
Keywords: Controlled release fertilizers; Controlled release fertilizers; Growth; Growth; Hevea brasiliensis; Hevea brasiliensis; Immature rubber; Immature rubber; Leaf nitrogen; Leaf nitrogen